2-Hydroxy-4-n-propoxy-5-bromoacetophenone oxime as an Analytical Reagent for Gravimetric Determination of V(V). Issue 2 (2009) - Nair, Ambily P.; Christine, J.
Abstract : 2-Hydroxy-4- n -propoxy-5-bromoacetophenone oxime (HnPBAO) was developed as a new analytical reagent for the gravimetric determination of pentavalent vanadium ion. In the pH range 4.0-6.0, the reagent gave a brown coloured precipitate with V(V). Job's method and Mole ratio method revealed that the stoichiometry of the complex is 1:1 (metal: ligand). Beer's law is obeyed up to 20.38 ppm of V(V). Molar absorptivity and Sandells sensitivity at 450 nm were found to be 10.22 × 10 2 L/mol/cm and 0.049 µg/cm 2 respectively. The stability constant of V(V)-HnPBAO complex is found to be 1.195 × 10 6 . Gibb's free energy change for complex formation reaction was found to be –8.34 kcal/mol. The reagent can be used for the analysis of vanadium in ferro-vanadium alloys.